The spatial dimension of population growth and its potential impact on the sustainable standard of green areas in the city for the period 2020-2025 Najaf Al-Ashraf case study (Journal of University of Babylon for Engineering Sciences, 2021)
The problem of green areas is considered one of the most complex urban planning problems in Najaf, under the influence of rapid population growth with relatively high growth rates of 2.6 percent in urban areas This is faced by an irrational use of empty and unused areas, and also  the fixity  of  residential neighborhoods in the city center and the expansion of the population on green areas and agricultural areas for housing purposes,  this will undoubtedly complicate the problem more. The study aims to develop solutions to this problem within an established master plan by calculating the current sustainable standard need for green areas based on the population size at the end of each year for each neighborhood alone. and forecasting them and showing the importance of their planning within an integrated urban planning system. The research adopted the descriptive analytical method of real historical data for each of the residents and spaces of residential neighborhoods that were divided into six districts in order to facilitate their study and analysis of their variables. And predicting what will happen in the growing sustainable standard of green areas for the next five years in the city center, and the most important result was that the decision makers have to provide new expansion areas outside the city center in the new neighborhoods camp, otherwise the green areas will disappear in the city center.